A holistic assessment of the use of emerging recycled concrete aggregates after a destructive earthquake: Mechanical, economic and environmental - Ulucan, Muhammed; Alyamac, Kursat Esat (Pergamon-Elsevier Science Ltd, 2022)
This study aims to examine the mechanical, environmental, and economic properties of recycled aggregate concretes produced using emerged recycled concrete aggregates from the buildings that were demolished in a controlled way after the 24 January 2020, Elazig-Sivrice earthquake. For this purpose, 24 series of recycled aggregate concretes were produced, water-to-cement ratios of 0.30-0.35-0.40-0.45-0.50, and cement dosages were chosen as 320-370-420 kg/m3. 100% recycled concrete aggregate was used in the prepared concrete mixtures. Analyses were made on the response surface method using the mixture ratios and test results of 24 series. The effectiveness of the developed models was examined on 6 Control recycled aggregate concrete. Then, Energy Consumption, Global Warming Potential, Waste Generation, and Abiotic Depletion were considered to assess the environmental impacts of recycled aggregate concretes. In order to make environmental and economic comparisons of recycled aggregate concretes and natural aggregate concretes according to these impact categories, 4 different scenarios were developed. Then, a detailed feasibility analysis was made for 4 different scenarios, and the economic results of recycled aggregate concretes and natural aggregate concretes were evaluated. Regarding the arisen millions of tons of waste materials and newly constructed buildings after the earthquake, recycling waste materials is considered crucial. Therefore, a holistic assessment was taken with this study, and the usability of recycled concrete aggregates was examined in detail.
Keywords: Recycled concrete aggregate; Recycled aggregate concrete; Earthquake; Construction and demolition waste; Life cycle assessment; Response surface method